2023
DOI: 10.3390/ph16010086
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol and Tapentadol Induce Conditioned Place Preference with a Differential Impact on Rewarding Memory and Incubation of Craving

Abstract: Tramadol and tapentadol, synthetic opioids commonly prescribed for moderate-to-severe pain, have a unique pharmacology that optimizes their analgesia and safety. However, they are not devoid of risks, presenting addictive, abuse, and dependence potential. While tramadol-reinforcing properties have been documented by various studies with human and animal models, including conditioned place preference (CPP) assays, no similar studies have been performed with tapentadol. In the present study, we performed CPP ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 57 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…Perananthan & Buckley, (11) works supported this nding and equally reported that users of tramadol sometimes grind the pills into tiny pieces to lick ("snorting"). Furthermore, Barbosa et al (19)agreed with this observation, and reported that licking was widespread due to the expected impact of doing so (noting the quick high, and feeling good). He found that nearly half (44%) of the participants "Always" stripped away foreign matter before licking, citing equal frequency either a desire for only the drug in the powder for a more immediate high (16%) or a dislike of the shell's properties, such as being sticky, irksome or scorching the nose, or experiencing dust in the nose (16%).…”
Section: Perceived Psychological Effects Of Tramadolmentioning
confidence: 96%
See 2 more Smart Citations
“…Perananthan & Buckley, (11) works supported this nding and equally reported that users of tramadol sometimes grind the pills into tiny pieces to lick ("snorting"). Furthermore, Barbosa et al (19)agreed with this observation, and reported that licking was widespread due to the expected impact of doing so (noting the quick high, and feeling good). He found that nearly half (44%) of the participants "Always" stripped away foreign matter before licking, citing equal frequency either a desire for only the drug in the powder for a more immediate high (16%) or a dislike of the shell's properties, such as being sticky, irksome or scorching the nose, or experiencing dust in the nose (16%).…”
Section: Perceived Psychological Effects Of Tramadolmentioning
confidence: 96%
“…The study also agrees with a study in Egypt about the causes of addiction, it was reported that, 50% of the participants studied were addicted as a result of peer in uence. Agani, in Saudi Arabia, it was reported that tramadol dependence began as a result of users acting under the in uence of their friends (19).…”
Section: Perceived Psychological Effects Of Tramadolmentioning
confidence: 99%
See 1 more Smart Citation
“…The six published articles highlight different aspects of the pharmacology and toxicology of several psychotropics; most of them are represented by opiates/opioids, e.g., tramadol [ 4 , 5 ], tapentadol [ 4 ], and fentanyl [ 6 ], but other categories here mentioned are selective serotonin reuptake inhibitor (SSRI) antidepressants [ 7 ], new psychoactive substances (NPSs) known as cathinones [ 8 ], and the hallucinogen drug psilocybin [ 9 ].…”
mentioning
confidence: 99%
“…The first paper [ 4 ] aimed to comparatively assess the rewarding and reinforcing properties of the synthetic opioids tramadol and tapentadol, at a therapeutic dose; the conditioned place preference (CPP) assay, a non-clinical animal paradigm of addiction potential in rats, was used. Both opioids showed short-term reinforcing properties; however, only tramadol showed the potential to induce drug memory and the incubation of craving several days after the last drug administration, suggesting that tapentadol has a lower propensity to induce dependence than tramadol.…”
mentioning
confidence: 99%